EU Accession to the ECHR – an Equation with Many Unknowns - Kazak, Tchetin (Yearbook of the Law Department, 2021)
This article aims to present the status of the accession project eight years after the CJEU‘s opinion: the long way it has come, what has been done since then, the possible obstacles that remain, starting with the long procedure of ratification of the accession agreement, including by countries outside the European Union. The vicissitudes that this project has gone through, as well as the challenges that continue to face it, turn its realization into an equation with many unknowns, for which solutions are still being sought and will be sought.